2011
DOI: 10.1039/c1sm05308f
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatible and biodegradable polymersomes for pH-triggered drug release

Abstract: Nano-sized biocompatible and biodegradable polymersomes were prepared based on poly(D,L-lactide)block-poly(2-methacryloyloxyethyl phosphorylcholine) (PLA-b-PMPC) diblock copolymers and applied for the release anti-cancer drugs. Hydrophobic doxorubicin (DOX) and hydrophilic doxorubicin hydrochloride (DOX$HCl) were successfully loaded into the polymersome membrane and polymersome interior, respectively. The in vitro release studies demonstrated that the release of DOX and DOX$HCl from polymersomes was highly pH-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 40 publications
1
43
0
Order By: Relevance
“…For example, biodegradable vesicles were prepared based on diblock copolymer poly(2-methacryloyloxyethyl phosphorylcholine)-block-poly(D,L-lactide) (PMPC-b-PLA). The in vitro release studies demonstrated that the release of DOX was significantly faster at mildly acidic pH (pH 5.0) compared to physiological pH (pH 7.4), which might be attributed to the hydrolysis of PLA [43]. Similarly, Luo et al prepared biodegradable 6-arm star poly(-caprolactone)-bpoly(2-methacryloyloxyethyl phosphorylcholine) (6sPCL-b-PMPC) [40].…”
Section: Phosphorylcholine (Pc) Modified Drug Nanocarriersmentioning
confidence: 96%
“…For example, biodegradable vesicles were prepared based on diblock copolymer poly(2-methacryloyloxyethyl phosphorylcholine)-block-poly(D,L-lactide) (PMPC-b-PLA). The in vitro release studies demonstrated that the release of DOX was significantly faster at mildly acidic pH (pH 5.0) compared to physiological pH (pH 7.4), which might be attributed to the hydrolysis of PLA [43]. Similarly, Luo et al prepared biodegradable 6-arm star poly(-caprolactone)-bpoly(2-methacryloyloxyethyl phosphorylcholine) (6sPCL-b-PMPC) [40].…”
Section: Phosphorylcholine (Pc) Modified Drug Nanocarriersmentioning
confidence: 96%
“…Wang et al [17] reported a poly(amino acid)-based amphiphilic copolymer drug-delivery system that exhibited a pH-dependent drug release profile in vitro; they found that the cumulative release of DOX was much faster at pH 5.0 than that at pH 7.4, and the DOX-loaded drug-delivery system had higher antitumor activity compared with that of free DOX. Liu et al [18] prepared poly(d,l-lactide)-block-poly(2-methacryloyloxyethyl phosphorylcholine) block copolymer and investigated the anticancer drug loading and release by using DOX and doxorubicin hydrochloride (DOX·HCl), and they found that the release of DOX and DOX·HCl from the block copolymer was highly pH-dependent, that is, the drug release was significantly faster at mildly acidic pH 5.0 compared with that at physiological pH 7.4. Furthermore, the DOX·HCl-loaded block copolymer exhibited faster drug release than the DOXloaded block copolymer under the same pH conditions.…”
Section: Organic-materials-based Ph-responsive Drug-delivery Systemsmentioning
confidence: 98%
“…These polymers named zwitterionic (ZI) can be easily tethered to a number of different surfaces and present attractive mechanical properties as well as thermal stability, specific chemical reactivity, and flexibility [133,134]. Due to their neutral net charge at physiological pH, ZI polymers have shown resistance to protein and cell binding, and thus a considerable part of the work on pH-responsive ZI surfaces concerns the fabrication of tunable antifouling coatings for biomaterials [135][136][137][138].…”
Section: Polymer Filmsmentioning
confidence: 99%